MEASURING CUSTOMERS’ ATTITUDE TOWARDS INNOVATIVE BANKING SERVICES OF PUBLIC AND PRIVATE SECTOR IN TIRUNELVELI DISTRICT - Regi, Bulomine; Franco, Eugine (International Journal of Research -GRANTHAALAYAH, 2016)
The beginning of empowerment of banking customers for their own transactions started with the evolution of ATMs as a delivery channel. The emergence of innovative banking services such as Self Service Banking Technologies (SSBT) i.e ATMs/ Debit Card, Credit Card, Internet Banking (IB), Mobile Banking (MB) with the concept of “Anytime and Anywhere Banking” has intensified the need of innovative banking services. With the advent of internet, the application of innovative banking services has been proven as an effective way to reduce the costs of operation for the financial institutions. Innovative banking services do allow banks to reduce expenditures on physical structures. It is believed that the e-banking will help the banks to cut costs, increase revenue and become more convenient for customers to do banking transactions. The methodology used in the study four banks were selected for the study and 90 customers were selected from each bank purposively those who are using innovative banking services namely ATM/Debit Card, Credit Card, Internet Banking and Mobile Banking. Four banks were selected based on Technological Award 2013-14. The select banks are State Bank of India, Canara Bank of public sector and ICICI and AXIS of private sector banks. The interview schedule was categorised into six parts using TAM extension model framed by the researcher. So it is important to anlayse the customers’ attitude towards innovative banking services of public and private sector banks.